Perancangan Strategi Dinas Perdagangan, Koperasi dan Usaha Kecil Menengah Kabupaten Barito Selatan untuk Usaha Mikro Kecil dan Menengah: Designing a Strategy for the Department of Trade, Cooperatives and Small and Medium Enterprises of South Barito Regency for Micro, Small and Medium Enterprises - Wahyunawati, Sri (Anterior Jurnal, 2024)
South Barito Disdagkop-UKM as the leading sector responsible for the development of MSMEs faces big challenges in resolving various problems faced by MSMEs. So you must have the ability to carry out work programs effectively and efficiently. This research aims to find out the strategy of the Department of Trade, Cooperatives, and Small and Medium Enterprises of South Barito Regency in developing Micro, Small, and Medium Enterprises (MSMEs). The analysis uses four matrices, namely the IFAS Matrix (Internal Factors Analysis Summary), EFAS (External Factors Analysis Summary), IE (Internal External Matrix), SWOT, and QSPM (Quantitative Strategic Planning Matrix). The results of the South Barito Disdagkop-UKM IE Matrix analysis are in the internal high external strong quadrant I, namely the Growth and Build position with the recommended strategy namely intensive or integrative. Selected strategy based on the QSPM matrix for South Barito Disdagkop-UKM Focus on work programs that prioritize innovations based on local industrial results (S1O1) with a STAS value of 3.99.